Isolation, full genomic characterization and neutralization-based human seroprevalence of Medjerda Valley virus, a novel sandfly-borne phlebovirus belonging to the Salehabad virus complex in northern Tunisia - Bichaud, Laurence; Dachraoui, Khalil; Alwassouf, Sulaf; Alkan, Cigdem; Mensi, Mohamed; Piorkowski, Géraldine; Sakhria, Sonia; Seston, Morgan; Fares, Wasfi; De Lamballerie, Xavier; Zhioua, Elyes; Charrel, Rémi N (The Journal of general virology, 2016)
A new phlebovirus, Medjerda Valley virus (MVV), was isolated from one pool of Phlebotomus sp. (Diptera; Psychodidae) sandflies trapped in the vicinity of the Utique site, northern Tunisia. Genetic analysis based on complete coding of genomic sequences of the three RNA segments indicated that MVV is most closely related to members of the Salehabad virus species, where it is the fourth virus for which the complete sequence is available. A seroprevalence study was performed to search for neutralizing antibodies in human sera in the same region. The results demonstrate that in this area, MVV can readily infect humans despite low seroprevalence rates. Salehabad species viruses have generally been considered to be a group of viruses with little medical or veterinary interest. This view deserves to be revisited according to our human seroprevalence results, together with high animal infection rate of Adana virus and recent evidence of human infection with Adria virus in Greece. Further studies are needed to investigate the capacity of each specific member of the Salehabad virus species to cause human or animal diseases.
Keywords: Humans; Antibodies, Neutralizing; Phylogeny; Molecular Sequence Data; Insect Vectors; molekulární sekvence - údaje; genom virový; neutralizující protilátky; horečka pappataci; séroepidemiologické studie; lidé; zvířata; Tunisia; Řecko; Genome, Viral; hmyz - vektory; Greece; fylogeneze; Phlebovirus; Phlebotomus Fever; Tunisko; protilátky virové; Antibodies, Viral; Animals; Psychodidae; Seroepidemiologic Studies